Regulatory Architecture of the Iron-Regulated fepD-ybdA Bidirectional Promoter Region in Escherichia coli - Christoffersen, Catherine A. (American Society for Microbiology, 2001)
The overlapping and opposing promoter elements for the Escherichia coli fepDGC operon and the ybdA gene (encoding a 43-kDa cytoplasmic membrane protein) within the enterobactin gene cluster were investigated by measuring the effects of site-specific mutations on transcript levels and on expression of reporter genes in a bidirectional transcriptional fusion vector. Primary promoter structures for the opposing transcripts overlapped extensively such that their −10 sequences were almost directly opposed on the two strands of the DNA helix and their +1 transcription start sites were only 23 bp apart. Relative to the E. coli consensus sequence, both promoters were poorly conserved at the −35 position and mutations which strengthened the −35 element of either promoter significantly enhanced its transcription, decreased that of the opposing promoter, and dramatically altered iron-mediated regulation of expression. Both the fepD and ybdA primary promoters were shown to require a 5′-TGn-3′ upstream extension of their −10 elements for optimal activities. Secondary promoters were identified for both fepD and ybdA, and their contributions to the overall expression levels were evaluated in these dual expression vector constructs. The data provided strong evidence that the architecture of the regulatory elements within the overlapping fepD and ybdA promoters is configured such that there is a direct competition for binding RNA polymerase and that the expression levels at these promoters are influenced not only by the activity of the opposing promoters but also by additional promoter sequence elements and perhaps accessory regulatory factors. Iron-mediated regulation of these promoters through the repressor protein Fur is a consequence of the relative promoter strengths and the position of an operator site that consists of two overlapping Fur-binding sequences in this compact regulatory region.